Prevalence and predictive factors of nocturia in patients with obstructive sleep apnea syndrome: A retrospective cross-sectional study. - Yeon Hak Chung; Jae Rim Kim; Su Jung Choi; Eun Yeon Joo (PLoS ONE, 2022)
Objectives Many patients with obstructive sleep apnea syndrome (OSAS) have nocturia. However, the predictive index of nocturia in patients with OSAS is currently not well known. We aimed to investigate the prevalence of nocturia in patients with OSAS and determine the factors that could predict nocturia in these patients. Methods In this retrospective cross-sectional study, we enrolled 1,264 untreated patients with OSAS (Apnea-Hypopnea Index, AHI ≥5/h on polysomnography [PSG]) from January 2017 to January 2020. Participants completed the Beck Depression Inventory-II (BDI-II), Pittsburgh Sleep Quality Index (PSQI), Insomnia Severity Index (ISI), and Epworth Sleepiness Scale. Participants were divided by sex and then subdivided into nocturia and non-nocturia groups according to the following question, "Do you go to the bathroom two times or more during your sleep?" Participants' characteristics and underlying disease were investigated, and all information, including PSG data, was compared between the two groups using the t-test or chi-square test. Results Overall, 35.2% (337/958) of male participants with OSAS and 59.8% (183/306) of female participants with OSAS had nocturia. The nocturia group was older; scored higher on the BDI-II, PSQI, and ISI; and had more underlying disease in both sexes. There was no difference in the AHI between the two groups among both sexes, but the hypoxia-related PSG parameters and sleep quality parameters, such as higher 90% oxygen desaturation index (90% ODI), lesser N3 sleep, and higher wakefulness after sleep onset, were worse among male participants with OSAS in the nocturia group than in the non-nocturia group. In multivariate logistic analysis, 90% ODI was an independent risk factor associated with nocturia in male participants with OSAS. Conclusions Considerable number of patients with OSAS had nocturia and poor sleep quality. Nocturia should be evaluated in male OSAS patients with severe hypoxia observed during sleep.